Method for one-step in-situ construction of double-defect photocatalyst

The two defects were introduced simultaneously by a one-step in-situ construction method, which solved the problem that existing photocatalysts were difficult to achieve multi-faceted performance improvement, and achieved efficient and controllable construction of photocatalysts, significantly improving their light absorption, carrier separation and Catalytic activity, suitable for large-scale production.

CN119500105APending Publication Date: 2025-02-25QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682712.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When existing photocatalysts improve their performance in many aspects such as light absorption, carrier separation and transmission, and catalytic reaction kinetics, it is difficult to achieve efficient and controllable multi-defect construction, resulting in unstable performance and underutilization of application potential.

Method used

Two different types of defects are introduced simultaneously by a one-step in-situ construction method, the specific steps include dissolving the first precursor, the second precursor, cetyl trimethylammonium bromide and NaOH in ethylene glycol, Ultrasonic and magnetic stirring followed by hydrothermal reaction, and finally a double defective photocatalyst was obtained by washing and vacuum drying.

Benefits of technology

The photocatalyst's light absorption capacity, carrier separation efficiency and catalytic activity have been significantly improved, and the overall performance and application potential of the photocatalyst are improved. At the same time, the preparation process is simplified, the production cost is reduced, and the stability and reuse are improved. performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for one-step in-situ construction of a double-defect photocatalyst, and relates to the technical field of photocatalysts, and the method comprises the following steps: dissolving a first precursor, a second precursor, hexadecyl trimethyl ammonium bromide and NaOH in ethylene glycol, transferring into a reaction kettle after dissolving, carrying out a hydrothermal reaction, cooling after the hydrothermal reaction is finished, washing, and carrying out vacuum drying to obtain the double-defect photocatalyst. The photocatalyst is obtained; the first precursor is selected from bismuth nitrate, and the second precursor is selected from one of sodium vanadate, sodium tungstate, sodium molybdate, sodium chromate and sodium selenate. According to the preparation method, effective generation of double defects can be realized in a single reaction step, the uniformity of a defect structure and the accuracy of proportion control are greatly improved, and the light absorption capacity, the carrier separation efficiency and the catalytic activity of the photocatalyst are remarkably improved, so that the photocatalytic activity and the selectivity of the photocatalyst are improved, the preparation process is simplified, and the preparation cost is reduced. The production cost is reduced, and the stability and reusability of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysts, and in particular to a method for in-situ construction of a double-defect photocatalyst in one step. Background Art

[0002] Photocatalysis is a green and environmentally friendly technology that uses light energy to accelerate chemical reactions. It has a wide range of applications in environmental purification, energy conversion and other fields. In recent years, with the increasingly serious energy crisis and environmental pollution problems, research on photocatalysis in the areas of solar water decomposition to produce hydrogen, air purification, and organic matter degradation has received more and more attention. As the core of the photocatalytic reaction, the performance of the photocatalyst directly determines the efficiency and application effect of the entire photocatalytic system. An efficient photocatalyst not only needs to have excellent light absorption ability, but also needs to have efficient photogenerated carrier separation and transmission capabilities, as well as strong catalytic activity and good stability.

[0003] At present, the defect regulation of photocatalysts is mainly focused on the introduction of single defects, and the specific technical solutions include two categories: physical methods and chemical methods. Physical methods such as annealing treatment and irradiation treatment introduce or adjust defects by changing the synthesis conditions of photocatalysts. For example, annealing treatment can promote the formation of oxygen vacancies in the crystal structure at high temperature, thereby improving photocatalytic activity. However, such methods are difficult to accurately control the type and concentration of defects, and are prone to introduce side defects, resulting in unstable material properties. Chemical methods include solvothermal method, chemical reduction method, doping method, etc., which introduce specific doping elements or induce defects through chemical reducing agents during the synthesis of photocatalysts. For example, nitrogen-doped titanium dioxide introduces nitrogen elements during the synthesis process to form nitrogen-doped defects, which can effectively extend the light absorption of TiO2 to the visible light range and improve its photocatalytic performance.

[0004] However, the existing single defect regulation method can usually only improve the photocatalytic performance in one aspect, and it is difficult to achieve comprehensive optimization of multiple aspects such as light absorption, carrier separation and transport, and catalytic reaction kinetics. The single defect structure is difficult to effectively promote the separation and transport of photogenerated carriers, and it is difficult to effectively inhibit the recombination of carriers, which limits the further improvement of photocatalytic efficiency; and the traditional defect regulation method is complex in the process of introducing multiple defects, lacks control means, and is difficult to achieve high controllability and repeatability. For example, the introduction of oxygen vacancies and doping elements separately is often complicated to operate, and it is difficult to accurately control the ratio and distribution of the two defects, resulting in uneven defect structure and affecting the overall performance of the catalyst; In addition, in the process of multi-defect regulation, due to the numerous process steps, it is easy to introduce side reactions or other impurity defects, thereby reducing the stability and reusability of the catalyst; The traditional multi-defect construction method has strict requirements on environmental conditions during the preparation process, poor process controllability, and high cost, which limits its feasibility of large-scale application. In addition, the introduction of single or multiple defects often cannot coordinate and optimize multiple performance indicators such as light absorption, carrier separation and transport, and catalytic reaction kinetics, and cannot comprehensively improve the overall efficiency and application potential of photocatalysts.

[0005] Therefore, how to simultaneously introduce multiple defects into photocatalysts can broaden the light absorption range, improve the carrier separation efficiency, and enhance the catalytic reaction activity, thereby significantly improving the overall performance and application potential of photocatalysts, and has become a new direction of current research. Summary of the invention

[0006] In view of the above shortcomings, the present invention proposes a method for constructing a double-defect photocatalyst, which effectively enhances the light absorption capacity of the photocatalyst, improves the carrier separation efficiency, and improves the kinetic performance of the catalytic reaction by simultaneously introducing two different types of defects, thereby significantly improving the overall performance and application potential of the photocatalyst, overcoming the above shortcomings in the prior art, and specifically comprising the following steps:

[0007] (1) dissolving the first precursor, the second precursor, hexadecyltrimethylammonium bromide and NaOH in ethylene glycol, ultrasonicating for 0.3-0.6 h at room temperature, and magnetically stirring for 3-5 h to obtain a mixed reagent;

[0008] (2) transferring the mixed reagents in step S1 into a reaction kettle for hydrothermal reaction;

[0009] (3) After the hydrothermal reaction in step S2 is completed and cooled, a defective sample is obtained, which is washed several times with anhydrous ethanol and deionized water, and then vacuum dried at 55° C.-65° C. for 8 h-12 h to obtain the double-defect photocatalyst;

[0010] Wherein, the first precursor is selected from bismuth nitrate, and the second precursor is selected from one of sodium vanadate, sodium tungstate, sodium molybdate, sodium chromate and sodium selenate.

[0011] Preferably, the photocatalyst comprises one of double-defect bismuth tungstate, double-defect bismuth vanadate, double-defect bismuth molybdate, double-defect bismuth chromate and double-defect bismuth selenate.

[0012] Preferably, the mass ratio of the first precursor to hexadecyltrimethylammonium bromide is 0.5-5:0.05-0.2, and the mass ratio of the second precursor to hexadecyltrimethylammonium bromide is 0.1-1:0.05-0.2.

[0013] Preferably, the mass ratio of the first precursor to NaOH is 0.5-5:0.01-0.12, and the mass ratio of the second precursor to NaOH is 0.1-1:0.01-0.12.

[0014] Preferably, the mass concentration of the first precursor and the second precursor in the mixed reagent is 0.006-0.6 g / mL.

[0015] Preferably, the temperature of the hydrothermal reaction in step S2 is 100° C.-200° C., and the time is 10 h-48 h.

[0016] The present invention provides a one-step in-situ method for constructing a double-defect photocatalyst. Compared with the prior art, the method can achieve the effective generation of double defects in a single reaction step, realize the efficient and controllable construction of two defects, greatly improve the uniformity of the defect structure and the accuracy of the proportion control, and significantly improve the light absorption capacity, carrier separation efficiency and catalytic activity of the photocatalyst, thereby improving the photocatalytic activity and selectivity of the photocatalyst; at the same time, the in-situ construction strategy adopted by the present invention not only simplifies the preparation process and reduces the production cost, but also improves the stability and reusability of the catalyst. The method is highly operable and suitable for large-scale production, providing a more reliable solution for the practical application of photocatalysts. DETAILED DESCRIPTION

[0017] The following will be combined with specific examples to illustrate the one-step in-situ construction method for preparing a double-defect photocatalyst. It is understood by those skilled in the art that the following examples are only the preparation methods of the above-mentioned photocatalyst of the present invention and are not intended to limit the entirety thereof.

[0018] Some embodiments of the present invention provide a one-step in-situ method for constructing a double-defect photocatalyst, comprising the following steps:

[0019] (1) Weighing a first precursor, a second precursor, hexadecyltrimethylammonium bromide and NaOH, dissolving the first precursor, the second precursor, hexadecyltrimethylammonium bromide and NaOH in ethylene glycol, ultrasonicating for 0.3-0.6h at room temperature, and magnetically stirring for 3-5h to obtain a mixed reagent after complete dissolution; the mass ratio of the first precursor to hexadecyltrimethylammonium bromide is 0.5-5:0.05-0.2, and the mass ratio of the second precursor to hexadecyltrimethylammonium bromide is 0.1-1:0.05-0.2; the mass ratio of the first precursor to NaOH is 0.5-5:0.01-0.12, and the mass ratio of the second precursor to NaOH is 0.1-1:0.01-0.12; the mass concentration of the first precursor and the second precursor in the mixed reagent is 0.006-0.6g / mL;

[0020] (2) transferring the mixed reagents in step S1 into a polytetrafluoroethylene reactor for hydrothermal reaction at a temperature of 100° C. to 200° C. for a time of 10 h to 48 h;

[0021] (3) After the hydrothermal reaction in step S2 is completed and cooled, a defective sample is obtained, which is washed several times with anhydrous ethanol and deionized water, and then vacuum dried at 55° C.-65° C. for 8 h-12 h to obtain the double-defect photocatalyst;

[0022] The first precursor is selected from bismuth nitrate, and the second precursor is selected from one of sodium vanadate, sodium tungstate, sodium molybdate, sodium chromate and sodium selenate.

[0023] The double-defect photocatalyst includes one of double-defect bismuth tungstate, double-defect bismuth vanadate, double-defect bismuth molybdate, double-defect bismuth chromate and double-defect bismuth selenate.

[0024] Example 1

[0025] Weigh 1.94 g of bismuth nitrate (Bi(NO3)3·5H2O), 0.658 g of sodium tungstate (Na2WO4·2H2O), 0.12 g of hexadecyltrimethylammonium bromide and 0.08 g of NaOH and dissolve them in 60 mL of ethylene glycol. Ultrasonicate for 0.5 h at room temperature and magnetically stir for 4 h to obtain a mixed reagent after complete dissolution. Then, the mixed reagent is transferred into a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 180 ° C for 24 h. After cooling, it is washed three times with anhydrous ethanol and deionized water, and vacuum dried at 60 ° C for 10 h.

[0026] sample <![CDATA[n Bi :n W :n O ]]> <![CDATA[Bi2WO6-V w / O ]]> 2.00:0.88:5.67

[0027] It can be seen from the above table that in the synthesized double-defect bismuth tungstate, the molar ratio of bismuth, tungsten and oxygen atoms is 2.00:0.88:5.67. Compared with the 2:1:6 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth tungstate is successfully prepared.

[0028] Example 2

[0029] Weigh 2.21g bismuth nitrate (Bi(NO3)3·5H2O), 0.566g sodium vanadate (NaVO3), 0.12g hexadecyltrimethylammonium bromide and 0.08g NaOH and dissolve them in 40mL ethylene glycol. Ultrasonicate for 0.5h at room temperature and magnetically stir for 4h to obtain a mixed reagent after complete dissolution. Then transfer the mixed reagent into a 100mL polytetrafluoroethylene reactor and hydrothermally react at 180℃ for 24h. After cooling, wash with anhydrous ethanol and deionized water three times and vacuum dry at 60℃ for 10h.

[0030] sample <![CDATA[n V :n W :n O ]]> <![CDATA[BiVO4-V w / O ]]> 1.00:0.86:3.64

[0031] It can be seen from the above table that in the synthesized double-defect bismuth vanadate, the molar ratio of vanadium, tungsten and oxygen atoms is 1.00:0.86:3.64. Compared with the 1:1:4 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth vanadate was successfully prepared.

[0032] Example 3

[0033] Weigh 1.94 g of bismuth nitrate (Bi(NO3)3·5H2O), 0.658 g of sodium tungstate (Na2WO4·2H2O), 0.12 g of hexadecyltrimethylammonium bromide and 0.04 g of NaOH and dissolve them in 30 mL of ethylene glycol. Ultrasonicate for 0.5 h at room temperature and magnetically stir for 4 h to obtain a mixed reagent after complete dissolution. Then, the mixed reagent is transferred into a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 180°C for 24 h. After cooling, it is washed three times with anhydrous ethanol and deionized water, and vacuum dried at 60°C for 10 h.

[0034] sample <![CDATA[n Bi :n W :n O ]]> <![CDATA[Bi2WO6-V w / O ]]> 2.00:0.92:5.83

[0035] It can be seen from the above table that in the synthesized double-defect bismuth tungstate, the molar ratio of bismuth, tungsten and oxygen atoms is 2.00:0.92:5.83. Compared with the 2:1:6 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth tungstate is successfully prepared.

[0036] Example 4

[0037] Weigh 2.21 g of bismuth nitrate (Bi(NO3)3·5H2O), 0.566 g of sodium vanadate (NaVO3), 0.12 g of hexadecyltrimethylammonium bromide and 0.04 g of NaOH and dissolve them in 20 mL of ethylene glycol. Ultrasonicate for 0.5 h at room temperature and magnetically stir for 4 h to obtain a mixed reagent after complete dissolution. Then, the mixed reagent is transferred into a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 180 ° C for 24 h. After cooling, it is washed three times with anhydrous ethanol and deionized water, and vacuum dried at 60 ° C for 10 h.

[0038] sample <![CDATA[n V :n W :n O ]]> <![CDATA[BiVO4-V w / O ]]> 1.00:0.95:3.89

[0039] It can be seen from the above table that in the synthesized double-defect bismuth vanadate, the molar ratio of vanadium, tungsten and oxygen atoms is 1.00:0.95:3.89. Compared with the 1:1:4 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth vanadate was successfully prepared.

[0040] Example 5

[0041] Weigh 1.94 g of bismuth nitrate (Bi(NO3)3·5H2O), 0.658 g of sodium tungstate (Na2WO4·2H2O), 0.12 g of hexadecyltrimethylammonium bromide and 0.08 g of NaOH and dissolve them in 60 mL of ethylene glycol. Ultrasonicate for 0.5 h at room temperature and magnetically stir for 4 h to obtain a mixed reagent after complete dissolution. Then, the mixed reagent is transferred into a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 130 ° C for 12 h. After cooling, it is washed three times with anhydrous ethanol and deionized water, and vacuum dried at 60 ° C for 10 h.

[0042] sample <![CDATA[n Bi :n W :n O ]]> <![CDATA[Bi2WO6-V w / O ]]> 2.00:0.95:5.90

[0043] It can be seen from the above table that in the synthesized double-defect bismuth tungstate, the molar ratio of bismuth, tungsten and oxygen atoms is 2.00:0.95:5.90. Compared with the 2:1:6 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth tungstate is successfully prepared.

[0044] Example 6

[0045] Weigh 2.21 g of bismuth nitrate (Bi(NO3)3·5H2O), 0.566 g of sodium vanadate (NaVO3), 0.12 g of hexadecyltrimethylammonium bromide and 0.08 g of NaOH and dissolve them in 40 mL of ethylene glycol. Ultrasonicate for 0.5 h at room temperature and magnetically stir for 4 h to obtain a mixed reagent after complete dissolution. Then, the mixed reagent is transferred into a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 130 ° C for 12 h. After cooling, it is washed three times with anhydrous ethanol and deionized water, and vacuum dried at 60 ° C for 10 h.

[0046] sample <![CDATA[n V :n W :n O ]]> <![CDATA[BiVO4-V w / O ]]> 1.00:0.92:3.89

[0047] It can be seen from the above table that in the synthesized double-defect bismuth vanadate, the molar ratio of vanadium, tungsten and oxygen atoms is 1.00:0.92:3.89. Compared with the 1:1:4 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth vanadate was successfully prepared.

[0048] Example 7

[0049] Weigh 4.32 g of bismuth nitrate (Bi(NO3)3·5H2O), 0.856 g of sodium tungstate (Na2WO4·2H2O), 0.12 g of hexadecyltrimethylammonium bromide and 0.08 g of NaOH and dissolve them in 60 mL of ethylene glycol. Ultrasonicate for 0.5 h at room temperature and magnetically stir for 4 h to obtain a mixed reagent after complete dissolution. Then, the mixed reagent is transferred into a 100 mL polytetrafluoroethylene reactor and hydrothermally reacted at 180°C for 24 h. After cooling, it is washed three times with anhydrous ethanol and deionized water, and vacuum dried at 60°C for 10 h.

[0050] sample <![CDATA[n Bi :n W :n O ]]> <![CDATA[Bi2WO6-V w / O ]]> 2.00:0.86:5.63

[0051] It can be seen from the above table that in the synthesized double-defect bismuth tungstate, the molar ratio of bismuth, tungsten and oxygen atoms is 2.00:0.86:5.63. Compared with the 2:1:6 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth tungstate is successfully prepared.

[0052] Example 8

[0053] Weigh 4.67g of bismuth nitrate (Bi(NO3)3·5H2O), 0.810g of sodium vanadate (NaVO3), 0.12g of hexadecyltrimethylammonium bromide and 0.08g of NaOH and dissolve them in 40mL of ethylene glycol. Ultrasonicate for 0.5h at room temperature and magnetically stir for 4h to obtain a mixed reagent after complete dissolution. Then, the mixed reagent is transferred into a 100mL polytetrafluoroethylene reactor and hydrothermally reacted at 180℃ for 24h. After cooling, it is washed three times with anhydrous ethanol and deionized water, and vacuum dried at 60℃ for 10h.

[0054] sample <![CDATA[n V :n W :n O ]]> <![CDATA[BiVO4-V w / O ]]> 1.00:0.81:3.59

[0055] It can be seen from the above table that in the synthesized double-defect bismuth vanadate, the molar ratio of vanadium, tungsten and oxygen atoms is 1.00:0.81:3.59. Compared with the 1:1:4 of the bulk sample, there is a decrease in the molar amount of tungsten and oxygen, indicating that the double-defect bismuth vanadate was successfully prepared.

[0056] The present invention provides a one-step in-situ method for constructing a double-defect photocatalyst. Compared with the prior art, the method can achieve the effective generation of double defects in a single reaction step, realize the efficient and controllable construction of two defects, greatly improve the uniformity of the defect structure and the accuracy of the proportion control, and significantly improve the light absorption capacity, carrier separation efficiency and catalytic activity of the photocatalyst, thereby improving the photocatalytic activity and selectivity of the photocatalyst; at the same time, the in-situ construction strategy adopted by the present invention not only simplifies the preparation process and reduces the production cost, but also improves the stability and reusability of the catalyst. The method is highly operable and suitable for large-scale production, providing a more reliable solution for the practical application of photocatalysts.

[0057] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A one-step in-situ method for constructing a double-defect photocatalyst, characterized in that: The steps include: (1) dissolving a first precursor, a second precursor, hexadecyltrimethylammonium bromide and NaOH in ethylene glycol to obtain a mixed reagent; (2) transferring the mixed reagents in step S1 into a reaction kettle for hydrothermal reaction; (3) After the hydrothermal reaction in step S2 is completed and cooled, a defect sample is obtained, and the defect sample is washed and vacuum dried to obtain the double-defect photocatalyst; Wherein, the first precursor is selected from bismuth nitrate, and the second precursor is selected from one of sodium vanadate, sodium tungstate, sodium molybdate, sodium chromate and sodium selenate.

2. The one-step in-situ construction method of a double-defect photocatalyst according to claim 1, characterized in that: The double-defect photocatalyst includes one of double-defect bismuth tungstate, double-defect bismuth vanadate, double-defect bismuth molybdate, double-defect bismuth chromate and double-defect bismuth selenate.

3. The method for constructing a double-defect photocatalyst in-situ in one step according to claim 1, characterized in that: The mass ratio of the first precursor to hexadecyltrimethylammonium bromide is 0.5-5:0.05-0.2, and the mass ratio of the second precursor to hexadecyltrimethylammonium bromide is 0.1-1:0.05-0.

2.

4. The method for constructing a double-defect photocatalyst in situ in one step according to claim 1, characterized in that: The mass ratio of the first precursor to NaOH is 0.5-5:0.01-0.12, and the mass ratio of the second precursor to NaOH is 0.1-1:0.01-0.

12.

5. The method for constructing a double-defect photocatalyst in-situ in one step according to claim 1, characterized in that: The mass concentration of the first precursor and the second precursor in the mixed reagent is 0.006 g / mL-0.6 g / mL in total.

6. The method for constructing a double-defect photocatalyst in-situ in one step according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step S2 is 100° C.-200° C., and the time is 10 h-48 h.